Prevalence of depression, anxiety, and stress among students enrolled at King Khalid University: a cross-sectional study - Abdulaziz M. Al-Garni; Ayed A. Shati; Nora A. Almonawar; Ghadi M. Alamri; Lujain A. Alasmre; Thamraa N. Saad; Faisal M. Alshehri; Esraa Abdellatif Hammouda; Ramy Mohammed Ghazy (BMC Public Health)
Abstract Background University students are more likely to experience mental disorders. This study aimed to assess the prevalence of depression, anxiety, and stress among health and non-health university students at King Khalid University students, Abha, Kingdom of Saudi Arabia. Methods An anonymous validated short form of Arabic questionnaire of the depression, anxiety, and stress scale (DASS-21) survey was distributed online on social media platforms and through face-to-face interview for 1700 students from March 1st to May 31st 2024. A multivariate linear regression model was used to examine the relationships between the independent variables (age, gender, academic year, and study field) and the dependent variables (depression, anxiety, and stress). Results More than half of the surveyed students (72.8%) were females. The age distribution reveals that the majority of students (71.4%) fall within the 20–25 years old, 22.6% were in their third year, and more than half (58.6%) pursued studies in non-health science disciplines. Almost 12% experienced moderate stress and 39% suffered from moderate, severe, and extremely severe anxiety, while 29.5% had moderate to severe depression. Youths younger than 25 years were at higher risk of experiencing depression (45.14% vs. 32.32% P = 0.024), stress (46.87% vs. 33.33%, P = 0.034), and anxiety than older ages (55.52% vs.43.43%, P = 0.019). Females also suffered more stress (48.47% vs. 38.53%, P = 0.0001), and anxiety (58.32 vs. 48.48%, P = 0.0001) than males. The correlations between depression and anxiety (0.75), depression and stress (0.83), and anxiety and stress (0.81) all indicate very strong positive correlations, with all tests being highly significant (P < 0.001). Regression analysis revealed that older age was associated with lower depression scores (P = 0.017), while female gender was associated with higher anxiety and stress scores (P < 0.001 for both). Conclusion The findings highlight the urgent need for regular screening and monitoring of students’ mental health status at King Khalid University. Implementing targeted mental health interventional programs is essential to help students to cope with different stressors with a particular focus on addressing the heightened challenges faced by female students.